2009
DOI: 10.1002/jccs.200900028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spiro‐Heterocycles with the Thiazolidinone Moiety from Nitrilimines

Abstract: The 2‐phenylimino‐1,3‐thiazolidin‐4‐one 2 was obtained by thermal cyclization of 4‐amino‐5‐phen‐yl‐3, 5‐thiaaza‐4‐pentenoic acid 1 using DCC as dehydration agent. Treatment of 2‐phenylimino‐1,3‐thiazolidin‐4‐one 2 with various hydrazonoyl halides 3 (nitrilimines 4 precursor) yielded 6‐aryl‐9‐phenyl‐8‐substituted‐1,4,6,7,9‐thiatetrazaspiro‐[4.4]non‐7‐en‐3‐ones 5a‐1. Both analytical and spectroscopic data of all the synthesized compounds are in full agreement with the proposed structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Earlier, it was reported that the cycloaddition of nitrile imines to the C=N bond of 2-iminothiazolidine-4-ones makes it possible to obtain a spiro-joined product containing the unaffected thiazolidine cycle [ 26 ] ( Scheme 6 a). Meanwhile, the reactions of diphenyl nitrile imine with 5-arylidene-substituted 2-iminothiazolidine-4-one resulted in the formation of a product of the sequential addition of two dipole molecules along both exocyclic double bonds C=N and C=S, which were formed as a result of the rearrangement of the intermediate spiro compound [ 27 ] ( Scheme 6 b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier, it was reported that the cycloaddition of nitrile imines to the C=N bond of 2-iminothiazolidine-4-ones makes it possible to obtain a spiro-joined product containing the unaffected thiazolidine cycle [ 26 ] ( Scheme 6 a). Meanwhile, the reactions of diphenyl nitrile imine with 5-arylidene-substituted 2-iminothiazolidine-4-one resulted in the formation of a product of the sequential addition of two dipole molecules along both exocyclic double bonds C=N and C=S, which were formed as a result of the rearrangement of the intermediate spiro compound [ 27 ] ( Scheme 6 b).…”
Section: Resultsmentioning
confidence: 99%
“… Reactions of nitrilimines with 2-iminothiazolidine-4-one ( a ) and its 5-arylidene derivative ( b ) [ 26 , 27 ]. …”
Section: Figures Schemes and Tablesmentioning
confidence: 99%
See 2 more Smart Citations
“…While in the second step, the Nitrogen atom of Schiff’s base undergoes attack by a sulfur nucleophile (thioglycolic acid) followed by intramolecular cyclization and elimination of water in the presence of DCC (N,N′-Dicyclohexylcarbodiimide). The DCC is used to accelerate the intramolecular cyclization which results in faster reaction and improved yield [32] , [33] .
Scheme 1 Scheme for the synthesis of 2-( R - phenyl)-3-[(4-methylphenyl)sulfonyl]-1,3-thiazolidin-4-one derivatives 5 (a-t).
…”
Section: Resultsmentioning
confidence: 99%